Computational Linguistics and Intelligent Text Processing 14th International Conference, CICLing 2013, Samos, Greece, March 24-30, 2013, Proceedings, Part I - Gelbukh, Alexander; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This two-volume set, consisting of LNCS 7816 and LNCS 7817, constitutes the thoroughly refereed proceedings of the 13th International Conference on Computer Linguistics and Intelligent Processing, CICLING 2013, held on Samos, Greece, in March 2013. The total of 91 contributions presented was carefully reviewed and selected for inclusion in the proceedings. The papers are organized in topical sections named: general techniques; lexical resources; morphology and tokenization; syntax and named entity recognition; word sense disambiguation and coreference resolution; semantics and discourse; sentiment, polarity, subjectivity, and opinion; machine translation and multilingualism; text mining, information extraction, and information retrieval; text summarization; stylometry and text simplification; and applications.
General Techniques -- Unsupervised Feature Adaptation for Cross-Domain NLP with an Application to Compositionality Grading -- Syntactic Dependency-Based N-grams: More Evidence of Usefulness in Classification -- Lexical Resources -- A Quick Tour of BabelNet 1.1 (Invited paper) -- Automatic Pipeline Construction for Real-Time Annotation -- A Multilingual GRUG Treebank for Underresourced Languages -- Creating an Annotated Corpus for Extracting Canonical Citations from Classics-Related Texts by Using Active Annotation -- Approaches of Anonymisation of an SMS Corpus -- A Corpus Based Approach for the Automatic Creation of Arabic Broken Plural Dictionaries -- Temporal Classifiers for Predicting the Expansion of Medical Subject Headings -- Knowledge Discovery on Incompatibility of Medical Concepts -- Extraction of Part-Whole Relations from Turkish Corpora -- Chinese Terminology Extraction Using EM-Based Transfer Learning Method -- Orthographic Transcription for Spoken Tunisian Arabic -- Morphology and Tokenization -- An Improved Stemming Approach Using HMM for a Highly Inflectional Language -- Semi-automatic Acquisition of Two-Level Morphological Rules for Iban Language -- Finite State Morphology for Amazigh Language -- New Perspectives in Sinographic Language Processing through the Use of Character Structure -- The Application of Kalman Filter Based Human-Computer Learning Model to Chinese Word Segmentation -- Machine Learning for High-Quality Tokenization Replicating Variable Tokenization Schemes -- Syntax and Named Entity Recognition Structural Prediction in Incremental Dependency Parsing -- Semi-supervised Constituent Grammar Induction Based on Text Chunking Information -- Turkish Constituent Chunking with Morphological and Contextual Features -- Enhancing Czech Parsing with Verb Valency Frames -- An Automatic Approach to Treebank Error Detection Using a Dependency Parser -- Topic-Oriented Words as Features for Named Entity Recognition (Best Paper Award, Second Place) -- Named Entities in Judicial Transcriptions: Extended Conditional Random Fields -- Introducing Baselines for Russian Named Entity Recognition -- Word Sense Disambiguation and Coreference Resolution Five Languages Are Better Than One: An Attempt to Bypass the Data Acquisition Bottleneck for WSD (Best Paper Award, Third Place) -- Analyzing the Sense Distribution of Concordances Obtained by Web as Corpus Approach -- MaxMax: A Graph-Based Soft Clustering Algorithm Applied to Word Sense Induction -- A Model of Word Similarity Based on Structural Alignment of Subject-Verb-Object Triples -- Coreference Annotation Schema for an Inflectional Language -- Exploring Coreference Uncertainty of Generically Extracted Event Mentions -- Semantics and Discourse -- LIARc: Labeling Implicit ARguments in Spanish Deverbal Nominalizations -- Automatic Detection of Idiomatic Clauses (Best Paper Award, First Place) -- Evaluating the Results of Methods for Computing Semantic Relatedness -- Similarity Measures Based on Latent Dirichlet Allocation -- Evaluating the Premises and Results of Four Metaphor Identification Systems -- Determining the Conceptual Space of Metaphoric Expressions -- What is being Measured in an Information Graphic? -- Comparing Discourse Tree Structures -- Assessment of Different Workflow Strategies for Annotating Discourse Relations: A Case Study with HDRB -- Building a Discourse Parser for Informal Mathematical Discourse in the Context of a Controlled Natural Language -- Discriminative Learning of First-Order Weighted Abduction from Partial Discourse Explanations -- Facilitating the Analysis of Discourse Phenomena in an Interoperable NLP Platform.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computational linguistics; Computer Science; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Database Management; Computational Linguistics